Representations of The Gurkhas (Lahures) in Modernist Narratives - Bhandari, Nagendra Bahadur (Unity Journal, 2021)
The representation Gurkha soldier or Lahures in British military writings and Nepali modernist narratives vary drastically. The British writings expose their martial skill and strength with high degree of integrity and loyalty in different wars including the First and Second World Wars. For instances, Brian Houghton Hodgson’s “Origin and Classification of the Military Tribes of Nepal”, J. P. Cross’s In Gurkha Company: The British Army Gurkhas and John Pemble’s British Gurkha War reflect their gallantry and unconditional loyalty. On the contrary, Nepali modernist narratives unravel their personal loss, separation, unpatriotic feeling and irresponsibility. Such unpleasant connotations in Nepali literature appears in ‘Aamali Sodhlin ni’ (Mother May Ask), a song of Jhalak Man Gandharva, “Sipahi” (Soldier), a story of Bishweshwar Prasad Koirala, Sisirko Phul (Blue Mimosa), a novel of Bishnu Kumari Baiba ‘Parijat’ and poems of Bhupi Sherchan. This article explores drastically different types of the representation of the Gurkhas (Lahures) in British military writings and Nepali narratives, and the socio-political contexts of their representation. The social, cultural and political contexts of representation and the motives of the writers render variations in their representations. This article unfolds the connection between the representation of the Gurkhas (Lahures) and the condition under which they are represented. While doing so, this paper supports an instance of the representation of Gurkha soldiers as an ideological construct on ground of political and sociological phenomena.